MODL-08. OPTIMIZATION OF A NOVEL LOCAL DELIVERY SYSTEM FOR THE TREATMENTS OF SUPRATENTORIAL EPENDYMOMA. (4th December 2020) - Ruff, Lisa; Parkins, Chris; Terranova, Sabrina; Nathan, Erica; Kasapidou, Paraskevi; Lang, Renata; Scherman, Oren; Gilbertson, Richard J
Abstract: Ependymomas are the third most common paediatric brain tumour, incurable in up to 40% of cases. Until recently, ependymomas were regarded as a single disease group with all patients receiving combinations of maximal surgical resection and radiotherapy. Use of chemotherapy has been limited by the resistant nature of the tumour and poor access to tumours behind the blood brain barrier (BBB). It is now known that ependymoma comprises up to nine different molecular subgroups. One subgroup is characterized by a novel fusion protein, C11orf95-RELA, which acts as a potent driver of oncogenesis resulting in a poor prognosis. Here, we present the optimization of a novel drug delivery system that uses biodegradable hydrogels to deliver drugs with potent anti-ependymoma properties into post-resection cavity of supratentorial ependymoma. Our previous high-throughput in-vivo drug screens identified candidate ependymoma therapies with poor BBB penetrance properties. Using in-vitro delivery assays, we have confirmed and monitored the release of these compounds from the hydrogel. Additionally, we have implemented this delivery system in our preclinical mouse hospital in which mice receive standard-of-care surgery and radiotherapy. The efficacy of hydrogel-based delivery of these compounds is now being tested preclinically, in combination with radiotherapy. Treatment for ependymoma patients have not changed in the last 30 years and therefore an effective chemotherapy could add a great survival benefit to in the clinic.